Optimizing information efficiency in a direct-sequence mobile packet radio network. - Chandra, M.W (IEEE Transactions on communications)
We consider a direct-sequence multihop packet radio network using slotted ALOHA in a Rayleigh fading environment. We are interested in optimally choosing the transmission range, code rate, and slotted ALOHA transmission probability to be used by each node. We use a new performance measure, information efficiency, to analyze the network and show that the information efficiency of the low-cost mobile packet radio network can be improved approximately 20 fold by using the optimum parameters. We suggest a practical trellis-coded modulation scheme which comes close to realizing the theoretic limits found.